Efficacy of Remote Ischemic Conditioning (RIC) as an Adjunct to Percutaneous Coronary Intervention (PCI) in ST‑Elevation Myocardial Infarction (STEMI) Patients: A Meta‑Analysis of Randomised Controlled Trials - Ahmed, Faisal Wali; Ahmad Anees, Hafiz Muhammad; Besati, Sri Hari Yadav; Asghar, Umair; Bin Johari, Mohamad Khir; Koirala, Anil; Nazin Nabila, Sumaiya; Mustafa, Mahnoor; Latif, Rimsha; Kalim, Nimra; et al. (Journal of Neonatal Surgery, 2025)
Background:Remote ischemic conditioning (RIC), involving intermittent ischemia-reperfusion cycles in a distant limb, has emerged as a promising adjunctive strategy to reduce myocardial reperfusion injury during primary percutaneous coronary intervention (PCI) in ST-elevation myocardial infarction (STEMI) patients. Despite promising findings from early-phase studies, larger trials have reported conflicting results, necessitating an updated evaluation of its efficacy. Objective:To systematically assess the efficacy of RIC as an adjunct to PCI in reducing adverse clinical outcomes and improving cardiac function in STEMI patients. Methods:This meta-analysis adhered to PRISMA guidelines and included randomized controlled trials (RCTs) comparing RIC plus PCI versus PCI alone in adult STEMI patients. Searches were conducted across PubMed, Scopus, Cochrane CENTRAL, and Web of Science through June 2024. Primary outcomes included cardiac death and major adverse cardiac events (MACE); secondary outcomes were infarct size and left ventricular ejection fraction (LVEF). Data were pooled using a random-effects model, with relative risks (RR) and mean differences (MD) calculated alongside 95% confidence intervals (CI). Results:Three RCTs comprising 2,735 patients (1,372 in RIC, 1,363 in control) were included. While RIC did not significantly reduce cardiac death (RR = 0.88, 95% CI: 0.75–1.03; p = 0.11) or MACE (RR = 0.91, 95% CI: 0.78–1.07; p = 0.24), it significantly improved LVEF (MD = +3.2%, 95% CI: 1.1–5.3; p = 0.004). A non-significant trend toward reduced infarct size was observed (MD = −2.4g, 95% CI: −5.1 to 0.3; p = 0.08). Subgroup analysis revealed that repeated RIC protocols yielded a significant reduction in adverse events (RR = 0.81, 95% CI: 0.66–0.99; p = 0.04), suggesting frequency and timing may influence therapeutic benefit. Conclusion:Although RIC did not significantly impact mortality or MACE rates, it was associated with improved cardiac function as reflected by enhanced LVEF. Repeated RIC protocols may offer superior benefits compared to single-session strategies. These findings support the cardioprotective role of RIC as a non-invasive, cost-effective adjunct during PCI for STEMI patients. Further high-quality RCTs with standardised protocols and long-term follow-up are needed to confirm its clinical utility